Project Based Learning Module Development in Vocational High Schools - Isna Aulia Nur Habibah; Harti Harti; Tri Sudarwanto (PT ARRUS Intelektual Indonesia, 2022)
The purpose of this research is to produce a teaching material product, namely a project-basedthat is suitable for use for class X BDP students on learning outcomes of consumer behavior, sales service, and customer satisfaction. The basis for this development is because the subject of marketing basics is a new subject in the prototype curriculum at SMK N 1 Lamongan so that there are not many learning resources available to support learning activities. The development procedure uses the ADDIE model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The results showed that the teaching materials developed had met the appropriate and effective aspects. The results of the validity test show that the based learning84% in the very feasible category. The average result of the pretest of students reached 55 and the number of students completed was 0%, and the results of theposttest -based module project-based learning experienced an average increase of 85 and the students who completed 90%. gain score module project based learning is known to have an average gain score of 0.72 which is described or categorized as high. So it can be said that student learning outcomes increase because the gain score is > 0.3. module project-based learning is effective in improving student learning outcomes